THE IMPACT OF MARKETING STRATEGY ON COMPANY EFFICIENCY AND PROFITABILITY - Zhanna B. Musatova (Вестник Российского экономического университета имени Г. В. Плеханова)
Properly selected strategic benchmarks and target indicators of development, as well as the corresponding marketing strategy of the company will successfully affect its financial standing and profit. PIMS model (Profit Impact on Marketing Strategy) is a prototype of target analysis of company factors. The article describes the development of PIMS model, which includes indentifying factors affecting growth (or stabilization) of profit and related to marketing activity. The classic PIMS model embraces analysis of qualitative and quantitative information about the growth in company market share which can influence the indicators of investment efficiency. The author's research shows that traditional marketing mix that is taken into account PIMS methodology could and should be extended at the expense of factors describing customer loyalty.